The Effect of the Use of Civics Learning Models in Higher Education on Student Civic Intelligence - Aini, Dinda Nurul; A., Abdulkarim; Sapriya, Sapriya; Rahmat, Rahmat (Universitas of Muhammadiyah Makassar, 2025)
Civic Education (Civics) learning has an important role in Higher Education to shape students' civic intelligence. However, the use of inappropriate learning models cannot shape civic intelligence. This study aims to find an overview and influence of the Civics learning model commonly used in higher education on student civic intelligence. The method used is a survey with a quantitative approach with data collection techniques using questionnaires distributed to research samples, namely students on three campuses in Subang Regency. The results of the study provide an overview in general the Civics learning models that are widely used are case studies and discussions. This learning model does not have a significant effect on student civic intelligence. The use of case study and discussion learning models affects aspects of interpersonal interaction and tolerance for differences. However, this is not optimal in some areas of civic intelligence, especially related to creativity, social participation, and the ability to manage emotions. It is necessary to choose a more optimal learning model, such as a project-based learning model.